Lithium-cobalt co-doped nickel oxide-based ceramic material and preparation method thereof
Through the specific ratio and preparation method of lithium-cobalt co-doped nickel oxide-based ceramic materials, the problem of unbalanced performance of traditional ceramic materials is solved, and high dielectric constant, low loss, good insulation and high temperature stability are achieved, suitable for complex Electronic equipment.
Patent Information
- Application Number
- CN202411283676.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the process of improving a single performance, traditional dielectric ceramic materials ignore the balance and optimization of the overall performance of the material, resulting in insufficient dielectric performance, insulation performance, thermal stability and mechanical strength, which is difficult to meet the needs of complex working environments.
Using lithium-cobalt co-doped nickel oxide-based ceramic materials, the nano-scale particle structure is formed through specific proportional composition and preparation methods, including high-energy ball milling and spray drying technology of nickel oxide, lithium chloride, cobalt oxide, neodymium oxide and other components, Optimize the sintering process to improve dielectric properties and mechanical strength.
It achieves high dielectric constant and low dielectric loss, enhances insulation performance and thermal stability, improves the overall performance of the material, is suitable for high-frequency circuits and high-temperature environments, and extends the service life of electronic components.
Smart Images

Figure BDA0005042454340000091 
Figure BDA0005042454340000101
Abstract
Description
Technical Field
[0001] This invention relates to the field of dielectric materials technology, and in particular to a lithium-cobalt co-doped nickel oxide-based ceramic material and its preparation method. Background Technology
[0002] With the rapid development of electronic information technology, the demand for high-performance dielectric ceramic materials is increasing. Due to their excellent dielectric properties, insulation properties, and good thermal stability and mechanical strength, dielectric ceramic materials are widely used in capacitors, filters, microwave dielectric devices, integrated circuit substrates and other fields. The formulation design of traditional dielectric ceramic materials often focuses on improving a single performance, while ignoring the balance and optimization of the overall performance of the material. For example, some materials have a high dielectric constant, but a large dielectric loss, which is not conducive to applications in high-frequency circuits; while other materials have good insulation properties, but insufficient thermal stability and mechanical strength, making it difficult to meet the requirements of complex working environments.
[0003] Patent document CN106128758B discloses an improved semiconductor ceramic capacitor material, which is made from the following raw materials in parts by weight: 12-26 parts barium titanate, 5-17 parts neodymium oxide, 3-12 parts titanium dioxide, 15-35 parts nano-ceramic powder, 2-5 parts glass fiber, 2-9 parts silicon dioxide, 3-12 parts zinc oxide, 3-7 parts strontium titanate, 2-6 parts bismuth titanate, 2-5 parts nickel oxide, 3-7 parts manganese dioxide, 4-7 parts zinc ammonium chloride, 7-13 parts organic binder, 2-6 parts modifier, and 3-8 parts reducing agent. However, this preparation method has problems such as inaccurate component control and uneven microstructure, which affect the dielectric properties of the material. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides a lithium-cobalt co-doped nickel oxide-based ceramic material, comprising the following components by mass ratio: 40-60 parts nickel oxide (NiO), 8-15 parts lithium chloride (LiCl), 5-10 parts cobalt oxide (CoO), 1-5 parts neodymium oxide (Nd₂O₃), 3-8 parts silicon dioxide (SiO₂), 3-8 parts aluminum oxide (Al₂O₃), 0.5-3 parts beryllium oxide (BeO), 1-5 parts nano-ceramic powder, 0.5-3 parts manganese dioxide (MnO₂), 0.5-3 parts vanadium oxide (V₂O₅), 0.5-3 parts lanthanum oxide (La₂O₃), and 0.5-3 parts cerium oxide (CeO₂).
[0005] Preferably, a lithium-cobalt co-doped nickel oxide-based ceramic material comprises the following components by mass ratio: 40 parts nickel oxide (NiO), 8 parts lithium chloride (LiCl), 5 parts cobalt oxide (CoO), 1 part neodymium oxide (Nd2O3), 3 parts silicon dioxide (SiO2), 3 parts aluminum oxide (Al2O3), 0.5 parts beryllium oxide (BeO), 1 part nano-ceramic powder, 0.5 parts manganese dioxide (MnO2), 0.5 parts vanadium oxide (V2O5), 0.5 parts lanthanum oxide (La2O3), and 0.5 parts cerium oxide (CeO2).
[0006] Preferably, a lithium-cobalt co-doped nickel oxide-based ceramic material comprises the following components by mass ratio: 60 parts nickel oxide (NiO), 15 parts lithium chloride (LiCl), 10 parts cobalt oxide (CoO), 5 parts neodymium oxide (Nd2O3), 8 parts silicon dioxide (SiO2), 8 parts aluminum oxide (Al2O3), 3 parts beryllium oxide (BeO), 5 parts nano-ceramic powder, 3 parts manganese dioxide (MnO2), 3 parts vanadium oxide (V2O5), 3 parts lanthanum oxide (La2O3), and 3 parts cerium oxide (CeO2).
[0007] Preferably, a lithium-cobalt co-doped nickel oxide-based ceramic material comprises the following components by mass ratio: 50 parts nickel oxide (NiO), 8 parts lithium chloride (LiCl), 8 parts cobalt oxide (CoO), 3 parts neodymium oxide (Nd2O3), 5 parts silicon dioxide (SiO2), 5 parts aluminum oxide (Al2O3), 1.5 parts beryllium oxide (BeO), 3 parts nano-ceramic powder, 1.5 parts manganese dioxide (MnO2), 1.5 parts vanadium oxide (V2O5), 1.5 parts lanthanum oxide (La2O3), and 1.5 parts cerium oxide (CeO2).
[0008] Meanwhile, the present invention provides a method for preparing the lithium-cobalt co-doped nickel oxide-based ceramic material, as detailed below:
[0009] S1. Dissolve nickel oxide and lithium chloride in ethanol to obtain a nickel-lithium mixture for later use;
[0010] S2. Grind cobalt oxide, neodymium oxide, silicon dioxide, aluminum oxide, beryllium oxide, manganese dioxide, vanadium oxide, lanthanum oxide, and cerium oxide to micron-sized particles to obtain a mixture of micron-sized particles;
[0011] S3. After grinding the micron-sized particle mixture to nano-sized particles using a high-energy ball mill, add the nickel-lithium mixture and mix, then spray dry to prepare the precursor powder.
[0012] S4. After the precursor powder and nano-ceramic powder are mixed evenly, they are heated under inert gas protection to obtain gas phase ceramic material.
[0013] S5. Cooling allows vapor-phase ceramic material to be deposited, resulting in lithium-cobalt co-doped nickel oxide-based ceramic material.
[0014] S6. Cleaning.
[0015] Preferably, in step S1, the ratio of nickel oxide, lithium chloride, and ethanol is 1:8-10.
[0016] Preferably, in step S2, the particle size of the micron-sized particle mixture is 100-300 μm.
[0017] Preferably, in step S3, the nanoscale particle size is 100-300 nm.
[0018] Preferably, in step S4, the inert gas is argon.
[0019] Preferably, in step S4, the heating temperature under inert gas protection is 1100-1300℃, the heating time is 1.5-2.5h, and the pressure is 1300-1500Pa.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0021] 1. The lithium cobalt co-doped nickel oxide-based ceramic material provided in this invention has a high dielectric constant and a low dielectric loss. The high dielectric constant enables the material to greatly increase the capacitance value when used in electronic components, thereby improving the overall performance of electronic devices. At the same time, its low dielectric loss characteristics ensure the energy transmission efficiency in high-frequency circuits and reduce unnecessary energy loss.
[0022] 2. The lithium co-doped nickel oxide-based ceramic material dielectric ceramic material provided in this invention has aluminum oxide, silicon dioxide and other components added to it, which endow it with good insulation properties, effectively prevent current leakage, improve its safety and reliability, and is suitable for electronic equipment that requires high insulation.
[0023] 3. The lithium co-doped nickel oxide-based ceramic material dielectric ceramic material provided in this invention has added components such as beryllium oxide and aluminum oxide, which significantly improves the thermal stability and mechanical strength of the material. This allows the dielectric ceramic material to maintain stable performance under high temperature environment and withstand greater mechanical stress, thus extending the service life of electronic components.
[0024] 4. The lithium co-doped nickel oxide-based ceramic material dielectric ceramic material provided in this invention has added nano-ceramic powder, which not only promotes the uniform distribution of grains during sintering, but also reduces the sintering temperature, thereby reducing energy consumption and production costs.
[0025] 5. The lithium-cobalt co-doped nickel oxide-based ceramic material dielectric ceramic material provided in this invention comprises the following components: 40-60 parts of nickel oxide (NiO), 8-15 parts of lithium chloride (LiCl), 5-10 parts of cobalt oxide (CoO), 1-5 parts of neodymium oxide (Nd2O3), 3-8 parts of silicon dioxide (SiO2), 3-8 parts of aluminum oxide (Al2O3), 0.5-3 parts of beryllium oxide (BeO), 1-5 parts of nano-ceramic powder, 0.5-3 parts of manganese dioxide (MnO2), 0.5-3 parts of vanadium oxide (V2O5), 0.5-3 parts of lanthanum oxide (La2O3), and 0.5-3 parts of cerium oxide (CeO2). By optimizing the proportions of each component, problems such as uneven sintering and product performance fluctuations that may occur in traditional processes are avoided, thereby improving production efficiency and product consistency.
[0026] 6. This invention uses ethanol as a solvent to dissolve nickel oxide and lithium chloride, which not only improves the dispersibility and dissolution efficiency of the raw materials, but also simplifies the subsequent mixing steps and reduces energy consumption and pollution in the preparation process. At the same time, the high-energy ball milling technology is used to grind the nanoparticle mixture to the nanoscale particle size, ensuring the uniform distribution of doped elements and the formation of nanostructures, laying a good foundation for the subsequent preparation process.
[0027] 7. This invention prepares precursor powder using spray drying technology, achieving rapid drying of raw materials and uniform particle size distribution. This avoids problems such as agglomeration and uneven particle size distribution that may occur with traditional drying methods. In addition, after mixing the precursor powder with nano-ceramic powder, the mixture is heated under inert gas protection, which effectively prevents oxidation and contamination of the material at high temperatures, further improving the purity and uniformity of the material. Detailed Implementation
[0028] Example 1
[0029] To address the aforementioned technical problems, this invention provides a lithium-cobalt co-doped nickel oxide-based ceramic material, comprising the following components by mass ratio: 40 parts nickel oxide (NiO), 8 parts lithium chloride (LiCl), 5 parts cobalt oxide (CoO), 1 part neodymium oxide (Nd₂O₃), 3 parts silicon dioxide (SiO₂), 3 parts aluminum oxide (Al₂O₃), 0.5 parts beryllium oxide (BeO), 1 part nano-ceramic powder, 0.5 parts manganese dioxide (MnO₂), 0.5 parts vanadium oxide (V₂O₅), 0.5 parts lanthanum oxide (La₂O₃), and 0.5 parts cerium oxide (CeO₂).
[0030] Meanwhile, the present invention provides a method for preparing the lithium-cobalt co-doped nickel oxide-based ceramic material, as detailed below:
[0031] S1. Dissolve nickel oxide and lithium chloride in ethanol to obtain a nickel-lithium mixture for later use;
[0032] S2. Grind cobalt oxide, neodymium oxide, silicon dioxide, aluminum oxide, beryllium oxide, manganese dioxide, vanadium oxide, lanthanum oxide, and cerium oxide to micron-sized particles to obtain a mixture of micron-sized particles;
[0033] S3. After grinding the micron-sized particle mixture to nano-sized particles using a high-energy ball mill, add the nickel-lithium mixture and mix, then spray dry to prepare the precursor powder.
[0034] S4. After the precursor powder and nano-ceramic powder are mixed evenly, they are heated under inert gas protection to obtain gas phase ceramic material.
[0035] S5. Cooling allows vapor-phase ceramic material to be deposited, resulting in lithium-cobalt co-doped nickel oxide-based ceramic material.
[0036] S6. Cleaning.
[0037] Moreover, in step S1, the ratio of nickel oxide, lithium chloride and ethanol is 1:8.
[0038] Moreover, in step S2, the particle size of the micron-sized particle mixture is 100 μm.
[0039] Moreover, in step S3, the nanoscale particle size is 100 nm.
[0040] Furthermore, in step S4, the inert gas is argon.
[0041] Furthermore, in step S4, the heating temperature under inert gas protection is 1100°C, the heating time is 1.5 hours, and the pressure is 1300 Pa.
[0042] Example 2
[0043] To solve the above-mentioned technical problems, the present invention provides a lithium cobalt co-doped nickel oxide-based ceramic material, which comprises the following components by mass ratio: 60 parts of nickel oxide (NiO), 15 parts of lithium chloride (LiCl), 10 parts of cobalt oxide (CoO), 5 parts of neodymium oxide (Nd2O3), 8 parts of silicon dioxide (SiO2), 8 parts of aluminum oxide (Al2O3), 3 parts of beryllium oxide (BeO), 5 parts of nano-ceramic powder, 3 parts of manganese dioxide (MnO2), 3 parts of vanadium oxide (V2O5), 3 parts of lanthanum oxide (La2O3), and 3 parts of cerium oxide (CeO2).
[0044] Meanwhile, the present invention provides a method for preparing the lithium-cobalt co-doped nickel oxide-based ceramic material, as detailed below:
[0045] S1. Dissolve nickel oxide and lithium chloride in ethanol to obtain a nickel-lithium mixture for later use;
[0046] S2. Grind cobalt oxide, neodymium oxide, silicon dioxide, aluminum oxide, beryllium oxide, manganese dioxide, vanadium oxide, lanthanum oxide, and cerium oxide to micron-sized particles to obtain a mixture of micron-sized particles;
[0047] S3. After grinding the micron-sized particle mixture to nano-sized particles using a high-energy ball mill, add the nickel-lithium mixture and mix, then prepare the precursor powder by spray drying.
[0048] S4. After the precursor powder and nano-ceramic powder are mixed evenly, they are heated under inert gas protection to obtain gas phase ceramic material.
[0049] S5. Cooling allows vapor-phase ceramic material to be deposited, resulting in lithium-cobalt co-doped nickel oxide-based ceramic material.
[0050] S6. Cleaning.
[0051] Moreover, in step S1, the ratio of nickel oxide, lithium chloride and ethanol is 1:10.
[0052] Moreover, in step S2, the micron-sized particle size is 300 μm.
[0053] Moreover, in step S3, the nanoscale particle size is 300 nm.
[0054] Furthermore, in step S4, the inert gas is argon.
[0055] Furthermore, in step S4, the heating temperature under inert gas protection is 1300℃, the heating time is 2.5h, and the pressure is 1500Pa.
[0056] Example 3
[0057] To address the aforementioned technical problems, this invention provides a lithium-cobalt co-doped nickel oxide-based ceramic material, comprising the following components by mass ratio: 50 parts nickel oxide (NiO), 115 parts lithium chloride (LiCl), 8 parts cobalt oxide (CoO), 3 parts neodymium oxide (Nd₂O₃), 5 parts silicon dioxide (SiO₂), 5 parts aluminum oxide (Al₂O₃), 1.5 parts beryllium oxide (BeO), 3 parts nano-ceramic powder, 1.5 parts manganese dioxide (MnO₂), 1.5 parts vanadium oxide (V₂O₅), 1.5 parts lanthanum oxide (La₂O₃), and 1.5 parts cerium oxide (CeO₂).
[0058] Meanwhile, the present invention provides a method for preparing the lithium-cobalt co-doped nickel oxide-based ceramic material, as detailed below:
[0059] S1. Dissolve nickel oxide and lithium chloride in ethanol to obtain a nickel-lithium mixture for later use;
[0060] S2. Grind cobalt oxide, neodymium oxide, silicon dioxide, aluminum oxide, beryllium oxide, manganese dioxide, vanadium oxide, lanthanum oxide, and cerium oxide to micron-sized particles to obtain a mixture of micron-sized particles;
[0061] S3. After grinding the micron-sized particle mixture to nano-sized particles using a high-energy ball mill, add the nickel-lithium mixture and mix, then prepare the precursor powder by spray drying.
[0062] S4. After the precursor powder and nano-ceramic powder are mixed evenly, they are heated under inert gas protection to obtain gas phase ceramic material.
[0063] S5. Cooling allows vapor-phase ceramic material to be deposited, resulting in lithium-cobalt co-doped nickel oxide-based ceramic material.
[0064] S6. Cleaning.
[0065] Moreover, in step S1, the ratio of nickel oxide, lithium chloride and ethanol is 1:9.
[0066] Moreover, in step S2, the particle size of the micron-sized particle mixture is 200 μm.
[0067] Moreover, in step S3, the nanoscale particle size is 200 nm.
[0068] Furthermore, in step S4, the inert gas is argon.
[0069] Furthermore, in step S4, the heating temperature under inert gas protection is 1200℃, the heating time is 2 hours, and the pressure is 1400Pa.
[0070] Comparative Example 1
[0071] The difference between this comparative example and Example 3 is that no aluminum oxide was added in this comparative example.
[0072] The specific preparation method is as follows:
[0073] S1. Dissolve nickel oxide and lithium chloride in ethanol to obtain a nickel-lithium mixture for later use;
[0074] S2. Grind cobalt oxide, neodymium oxide, silicon dioxide, beryllium oxide, manganese dioxide, vanadium oxide, lanthanum oxide, and cerium oxide to micron-sized particles to obtain a mixture of micron-sized particles;
[0075] S3. After grinding the micron-sized particle mixture to nano-sized particles using a high-energy ball mill, add the nickel-lithium mixture and mix, then prepare the precursor powder by spray drying.
[0076] S4. After the precursor powder and nano-ceramic powder are mixed evenly, they are heated under inert gas protection to obtain gas phase ceramic material.
[0077] S5. Cooling allows vapor-phase ceramic material to be deposited, resulting in lithium-cobalt co-doped nickel oxide-based ceramic material.
[0078] S6. Cleaning.
[0079] Moreover, in step S1, the ratio of nickel oxide, lithium chloride and ethanol is 1:9.
[0080] Moreover, in step S2, the particle size of the micron-sized particle mixture is 200 μm.
[0081] Moreover, in step S3, the nanoscale particle size is 200 nm.
[0082] Furthermore, in step S4, the inert gas is argon.
[0083] Furthermore, in step S4, the heating temperature under inert gas protection is 1200℃, the heating time is 2 hours, and the pressure is 1400Pa.
[0084] Comparative Example 2
[0085] The difference between this comparative example and Example 3 is that no silicon dioxide was added in this comparative example.
[0086] The specific preparation method is as follows:
[0087] S1. Dissolve nickel oxide and lithium chloride in ethanol to obtain a nickel-lithium mixture for later use;
[0088] S2. Grind cobalt oxide, neodymium oxide, aluminum oxide, beryllium oxide, manganese dioxide, vanadium oxide, lanthanum oxide, and cerium oxide to micron-sized particles to obtain a mixture of micron-sized particles;
[0089] S3. After grinding the micron-sized particle mixture to nano-sized particles using a high-energy ball mill, add the nickel-lithium mixture and mix, then spray dry to prepare the precursor powder.
[0090] S4. After the precursor powder and nano-ceramic powder are mixed evenly, they are heated under inert gas protection to obtain gas phase ceramic material.
[0091] S5. Cooling allows vapor-phase ceramic material to be deposited, resulting in lithium-cobalt co-doped nickel oxide-based ceramic material.
[0092] S6. Cleaning.
[0093] Moreover, in step S1, the ratio of nickel oxide, lithium chloride and ethanol is 1:9.
[0094] Moreover, in step S2, the particle size of the micron-sized particle mixture is 200 μm.
[0095] Moreover, in step S3, the nanoscale particle size is 200 nm.
[0096] Furthermore, in step S4, the inert gas is argon.
[0097] Furthermore, in step S4, the heating temperature under inert gas protection is 1200℃, the heating time is 2 hours, and the pressure is 1400Pa.
[0098] Comparative Example 3
[0099] The difference between this comparative example and Example 3 is that no beryllium oxide was added in this comparative example.
[0100] The specific preparation method is as follows:
[0101] S1. Dissolve nickel oxide and lithium chloride in ethanol to obtain a nickel-lithium mixture for later use;
[0102] S2. Grind cobalt oxide, neodymium oxide, silicon dioxide, aluminum oxide, manganese dioxide, vanadium oxide, lanthanum oxide, and cerium oxide to micron-sized particles to obtain a mixture of micron-sized particles;
[0103] S3. After grinding the micron-sized particle mixture to nano-sized particles using a high-energy ball mill, add the nickel-lithium mixture and mix, then spray dry to prepare the precursor powder.
[0104] S4. After the precursor powder and nano-ceramic powder are mixed evenly, they are heated under inert gas protection to obtain gas phase ceramic material.
[0105] S5. Cooling allows vapor-phase ceramic material to be deposited, resulting in lithium-cobalt co-doped nickel oxide-based ceramic material.
[0106] S6. Cleaning.
[0107] Moreover, in step S1, the ratio of nickel oxide, lithium chloride and ethanol is 1:9.
[0108] Moreover, in step S2, the particle size of the micron-sized particle mixture is 200 μm.
[0109] Moreover, in step S3, the nanoscale particle size is 200 nm.
[0110] Furthermore, in step S4, the inert gas is argon.
[0111] Furthermore, in step S4, the heating temperature under inert gas protection is 1200℃, the heating time is 2 hours, and the pressure is 1400Pa.
[0112] Comparative Example 4
[0113] The difference between this comparative example and Example 3 is that no nano-ceramic powder was added in this comparative example.
[0114] The specific preparation method is as follows:
[0115] S1. Dissolve nickel oxide and lithium chloride in ethanol to obtain a nickel-lithium mixture for later use;
[0116] S2. Grind cobalt oxide, neodymium oxide, silicon dioxide, aluminum oxide, beryllium oxide, manganese dioxide, vanadium oxide, lanthanum oxide, and cerium oxide to micron-sized particles to obtain a mixture of micron-sized particles;
[0117] S3. After grinding the micron-sized particle mixture to nano-sized particles using a high-energy ball mill, add the nickel-lithium mixture and mix, then prepare the precursor powder by spray drying.
[0118] S4. The precursor powder is heated under inert gas protection to obtain vapor phase ceramic material;
[0119] S5. Cooling allows vapor-phase ceramic material to be deposited, resulting in lithium-cobalt co-doped nickel oxide-based ceramic material.
[0120] S6. Cleaning.
[0121] Moreover, in step S1, the ratio of nickel oxide, lithium chloride and ethanol is 1:9.
[0122] Moreover, in step S2, the particle size of the micron-sized particle mixture is 200 μm.
[0123] Moreover, in step S3, the nanoscale particle size is 200 nm.
[0124] Furthermore, in step S4, the inert gas is argon.
[0125] Furthermore, in step S4, the heating temperature under inert gas protection is 1200℃, the heating time is 2 hours, and the pressure is 1400Pa.
[0126] Comparative Example 5
[0127] The difference between this comparative example and Example 3 is that a traditional preparation method is used, as follows:
[0128] S1. Take 50 parts of nickel oxide (NiO), 115 parts of lithium chloride (LiCl), 8 parts of cobalt oxide (CoO), 3 parts of neodymium oxide (Nd2O3), 5 parts of silicon dioxide (SiO2), 5 parts of aluminum oxide (Al2O3), 1.5 parts of beryllium oxide (BeO), 3 parts of nano-ceramic powder, 1.5 parts of manganese dioxide (MnO2), 1.5 parts of vanadium oxide (V2O5), 1.5 parts of lanthanum oxide (La2O3), and 1.5 parts of cerium oxide (CeO2) and grind them in a ball mill to a particle size of 200μm, and mix them evenly.
[0129] S2. Sintering time is 2 hours at 1200℃ and 1400Pa.
[0130] Experimental Section
[0131] The lithium-cobalt co-doped nickel oxide-based ceramic materials prepared in Examples 1-3 and Comparative Examples 1-5 were fabricated into test blocks with a length of 100 mm, a width of 10 mm, and a thickness of 3 mm, respectively, and their properties were measured as follows:
[0132] 1. Dielectric constant: The dielectric constant of the test block was measured using an impedance analyzer. The dielectric constant (ε) = C·d / ε0·A, where C is the measured capacitance (farads), d is the thickness of the test block (meters), and ε0 is the dielectric constant in vacuum (approximately 8.854 × 10⁻⁶). -12 The dielectric constant is measured in farads per meter (Fd / m), where A is the area (square meters) of the contact between the test block and the electrode. The final measured dielectric constant is rounded to the nearest integer. The results are shown in Table 1.
[0133] 2. Dielectric loss tangent: The dielectric loss tangent of the test block was measured using an impedance analyzer. The dielectric loss tangent is 1 / ωRC, where C is the capacitance (farads), R is the equivalent series resistance (ohms), and ω is the angular frequency (radians / second). The measured dielectric loss tangent was rounded to the nearest integer. The results are shown in Table 1.
[0134] 3. Insulation resistance: The insulation resistance of the test block was measured by applying a voltage of 500V under the conditions of 25℃ and 60%RH using a megohmmeter. The measured insulation resistance was rounded to the nearest integer. The results are shown in Table 1.
[0135] 4. Thermal conductivity: The thermal conductivity of the test block was calculated using a thermal conductivity meter according to Fourier's law. The final measured thermal conductivity was rounded to the nearest integer. The results are shown in Table 1.
[0136] 5. Fracture toughness value: The specimen was subjected to a force of 10 kg (98 N) using the indentation method, and the crack length was measured.
[0137] Table 1. Performance Measurement of Dielectric Ceramic Materials
[0138]
[0139]
[0140] As shown in Table 1, the lithium-cobalt co-doped nickel oxide-based ceramic material prepared in this invention has a high dielectric constant and low dielectric loss. Furthermore, it exhibits good insulation properties, thermal stability, and mechanical strength. The high dielectric constant allows for a significant increase in capacitance when used in electronic components, thereby improving the overall performance of electronic devices. Simultaneously, its low dielectric loss ensures efficient energy transmission in high-frequency circuits, reducing unnecessary energy loss. Good insulation performance effectively prevents current leakage, enhancing safety and reliability, making it suitable for electronic devices requiring high insulation. The good thermal stability and mechanical strength allow the dielectric ceramic material to maintain stable performance even at high temperatures and withstand significant mechanical stress, extending the service life of electronic components.
Claims
1. A lithium-cobalt co-doped nickel oxide-based ceramic material, characterized in that: The composition includes the following components by mass ratio: 40-60 parts of nickel oxide, 8-15 parts of lithium chloride, 5-10 parts of cobalt oxide, 1-5 parts of neodymium oxide, 3-8 parts of silicon dioxide, 3-8 parts of aluminum oxide, 0.5-3 parts of beryllium oxide, 1-5 parts of nano-ceramic powder, 0.5-3 parts of manganese dioxide, 0.5-3 parts of vanadium oxide, 0.5-3 parts of lanthanum oxide and 0.5-3 parts of cerium oxide.
2. A lithium-cobalt co-doped nickel oxide-based ceramic material as claimed in claim 1, characterized in that: The composition is as follows: 40 parts of nickel oxide, 8 parts of lithium chloride, 5 parts of cobalt oxide, 1 part of neodymium oxide, 3 parts of silicon dioxide, 3 parts of aluminum oxide, 0.5 parts of beryllium oxide, 1 part of nano-ceramic powder, 0.5 parts of manganese dioxide, 0.5 parts of vanadium oxide, 0.5 parts of lanthanum oxide and 0.5 parts of cerium oxide.
3. The lithium-cobalt co-doped nickel oxide-based ceramic material according to claim 1, characterized in that: The composition is as follows: 60 parts of nickel oxide, 15 parts of lithium chloride, 10 parts of cobalt oxide, 5 parts of neodymium oxide, 8 parts of silicon dioxide, 8 parts of aluminum oxide, 3 parts of beryllium oxide, 5 parts of nano-ceramic powder, 3 parts of manganese dioxide, 3 parts of vanadium oxide, 3 parts of lanthanum oxide and 3 parts of cerium oxide.
4. The lithium-cobalt co-doped nickel oxide-based ceramic material according to claim 1, characterized in that: The composition is as follows: 50 parts of nickel oxide, 11 parts of lithium chloride, 8 parts of cobalt oxide, 3 parts of neodymium oxide, 5 parts of silicon dioxide, 5 parts of aluminum oxide, 1.5 parts of beryllium oxide, 3 parts of nano-ceramic powder, 1.5 parts of manganese dioxide, 1.5 parts of vanadium oxide, 1.5 parts of lanthanum oxide and 1.5 parts of cerium oxide.
5. A lithium-cobalt co-doped nickel oxide-based ceramic material according to any one of claims 1 to 4, characterized in that: The preparation method of the lithium-cobalt co-doped nickel oxide-based ceramic material is as follows: S1, dissolving nickel oxide and lithium chloride in ethanol to obtain a nickel-lithium mixed solution for standby use; S2, grinding cobalt oxide, neodymium oxide, silicon dioxide, aluminum oxide, beryllium oxide, manganese dioxide, vanadium oxide, lanthanum oxide, and cerium oxide to micron-sized particles to obtain a micron particle mixture; S3, grinding the micron particle mixture into nanometer-scale particle size by high-energy ball mill, adding nickel-lithium mixed solution and mixing, and then preparing precursor powder by spray drying; S4, after the precursor powder and the nano-ceramic powder are uniformly mixed, heating is carried out under the protection of an inert gas to obtain a gas-phase ceramic material; S5, cooling to deposit the vapor phase ceramic material to obtain a lithium-cobalt co-doped nickel oxide-based ceramic material; S6. Cleaning.
6. A lithium-cobalt co-doped nickel oxide-based ceramic material as claimed in claim 5, characterized in that: In the step S1, the material-liquid ratio of nickel oxide, lithium chloride and ethanol is 1:8-10.
7. The lithium-cobalt co-doped nickel oxide-based ceramic material according to claim 5, characterized in that: In the step S2, the particle size of the micron particle mixture is 100-300 μm.
8. The lithium-cobalt co-doped nickel oxide-based ceramic material according to claim 5, characterized in that: In the step S3, the nano-scale particle size is 100-300 nm.
9. The lithium-cobalt co-doped nickel oxide-based ceramic material according to claim 5, characterized in that: In the step S4, the inert gas is argon.
10. The lithium-cobalt co-doped nickel oxide-based ceramic material according to claim 5, characterized in that: In the step S4, the heating temperature under the protection of inert gas is 1100-1300° C., the heating time is 1.5-2.5 hours, and the pressure is 1300-1500 Pa.
Citation Information
Patent Citations
Li-Co co-doped nickel oxide-based ceramic material and preparation method thereof based on sol-gel method
CN102557589A
Improved semiconductor ceramic capacitor material and preparation method thereof
CN106128758A
Multifunctional coating and slurry for lithium ion battery, preparation methods for multifunctional coating and slurry, and lithium ion battery
CN106229474A
Cerium-zirconium doped polishing solution as well as preparation method and application thereof
CN112724836A
Method for preparing electronic phase change ceramic material by doping vanadium oxide with transition metal oxide
CN114538924A
